Management of Septic emboli in patients with infectious endocarditis. Issue 5 (17th April 2017) - Aalaei‐Andabili, Seyed Hossein; Martin, Tomas; Hess, Phillip; Hoh, Brian; Anderson, Meshka; Klodell, Charles T.; Beaver, Thomas M.
Abstract: Background and Aim: Septic emboli (SE) associated with infectious endocarditis (IE) can result in splenic abscesses and infectious intracranial aneurysms (IIA). We investigated the impact of SE on patient outcomes following surgery for IE. Method: From January‐2000 to October‐2015, all patients with surgical IE (n = 437) were evaluated for incidence and management of SE. Results: Overall SE was found in 46/437 (10.52%) patients (n = 17 spleen, 13 brain, and 16 both). No mortality was seen in the brain emboli groups, but in the splenic abscess group the in‐hospital mortality was 8.69% (n = 4); and was associated with Age >35 (OR = 2.63, 1.65‐4.20) and congestive heart failure (OR = 14.40, 1.23‐168.50). Patients with splenic emboli had excellent mid‐term outcome following discharge (100% survival at 4‐years). Splenic emboli requiring splenectomy was predicted by a >20 mm valve vegetation (OR = 1.37, 1.056‐1.77) and WBC >12000 cells/mm (OR = 5.58, 1.2‐26.3). No patient with streptococcus‐viridians infection had a nonviable spleen (OR = 0.67, 0.53‐0.85). Postoperative acute‐kidney‐injury was higher in the splenectomy group (45.45% vs 9%) (p = 0.027). There were 6 patients with symptomatic IIAs that required coiling/clipping which was associated with age <30 years, (OR = 6.09, 1.10‐33.55). Survival in patients with cerebral emboli decreased to 78% at 3‐4 years. Patients with both splenic and brain emboli had a 92% survival rate at 1‐year and 77% at 2‐4 years. Conclusion: Septic emboli is common in endocarditis patients. Patients with high preoperative WBC level and large valve vegetations require CT imaging of the spleen. Both spleen and brain interventions in the setting of IE can be performed safely with excellent early and mid‐term outcomes.